P250 Informing the pathway of COPD treatment (the IMPACT study): single inhaler triple therapy (FF/UMEC/VI) versus FF/VI in patients with COPD – cost-effectiveness in the UK. (December 2018) - Martin, A; Shah, D; Schroeder, M; Ndirangu, K; Risebrough, N; Anley, G; Okorogheye, G; Fenwick, E; Ismaila, AS
Abstract : Introduction and objectives: The IMPACT trial (NCT02164513 ) showed superior exacerbation reduction and lung function improvement with once-daily single inhaler triple therapy, fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) 100/62.5/22 µg, compared with once-daily FF/VI 100/22 µg, for patients with symptomatic COPD and a history of exacerbations. An economic model was developed to assess the cost-effectiveness of FF/UMEC/VI vs FF/VI from a UK NHS perspective, using results from IMPACT. Methods: The model combined a decision-tree for the trial period, with longer-term outcomes extrapolated via a Markov model with health states reflecting COPD severity and exacerbation history. Disease progression and exacerbation rates were determined by risk equations based on the 3 year Towards a Revolution in COPD Health study (TORCH, NCT00268216 ). The model was populated with baseline characteristics, efficacy and medication use from IMPACT, while healthcare resource use and utility estimates came from the literature. Medication and healthcare resource use were costed using UK drug prices and unit costs (2018 £). Results are for a lifetime horizon with costs and health outcomes (except life-years) discounted at 3.5%. Results: Treatment with FF/UMEC/VI, compared with FF/VI, resulted in fewer moderate and severe exacerbations (6.460 and 1.501 vs 6.686 and 1.528), more life-years (8.874 vs 8.577) increased quality-adjusted life years (QALYs, 6.565 vs 6.291) and higher total costs (£24 843 vs £23, 549). Patients receiving FF/UMEC/VI gained an additional 0.275 QALYs for an additional cost of £1, 294, compared to those receiving FF/VI, to give an incremental cost-effectiveness ratio (ICER) of £4712 per QALY gained. In deterministic sensitivity/scenario analyses, ICERs ranged from dominant to £7502 per QALY gained, with results most sensitive to drug acquisition costs, utility associated with moderate COPD, duration of treatment effect and time horizon. In probabilistic sensitivity analysis, the probability of FF/UMEC/VI being cost-effective vs FF/VI was 95% at a willingness-to-pay threshold of £20 000 per QALY. Conclusions: Treatment with FF/UMEC/VI was predicted to improve health outcomes and to be a cost-effective option for patients with symptomatic COPD and a history of exacerbations, when compared with FF/VI, in the UK. Funding: GSK (study number HO-17–17596). ICON Health Economics received funding from GSK to conduct the study only.